’THE RELATIONSHIP BETWEEN GESTATIONAL HYPERTENSION AND HEMOGLOBIN LEVELS AND THE INCIDENCE OF LOW BIRTH WEIGHT (LBW) - Hadi, Yuni Riska; Putri, Nadia Rahma; P., Lina Agustiana (STIKes RSPAD RSPAD Gatot Soebroto, 2025)
Low birth weight (LBW) infants are one of the main factors contributing to morbidity and mortality in the neonatal period. Gestational hypertension and hemoglobin levels during pregnancy are two maternal factors that can affect fetal growth and increase the risk of low birth weight babies. Analyzing the relationship between gestational hypertension and hemoglobin levels in pregnant women and its impact on the incidence of low birth weight babies at Blambangan Banyuwangi Regional General Hospital. This study implemented an observational analytical design using a cross-sectional approach. The study involved 41 mothers who had just given birth, selected using total sampling. The variables analyzed included gestational hypertension, hemoglobin levels, and the incidence of low birth weight. Data collection was conducted using observation sheets, and analysis was performed by applying the chi-square test at a significance level of α = 0.05. The results of the study on gestational hypertension show that the majority, namely 27 individuals, or 65.9% of the total sample, experienced hypertension. Hemoglobin level analysis indicates that the majority, namely 23 individuals, were within the normal range, covering 56.1% of the entire sample. Analysis of LBW cases indicated that the majority of babies had normal weight, with a total of 32 babies identified, covering 78% of the entire sample. Statistical analysis indicated a significant relationship between gestational hypertension and hemoglobin levels on LBW cases (p < 0.05). There exists a correlation between gestational hypertension and hemoglobin levels and the incidence of low birth weight infants. Regular monitoring of blood pressure and hemoglobin levels in pregnant women, as well as intensive education, are necessary to prevent the risk of low birth weight (LBW) babies.